2016
DOI: 10.18632/oncotarget.9235
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational regulation of the cleaved fragment of Par-4 in ovarian and endometrial cancer cells

Abstract: We recently reported the caspase3-dependent cleavage of Par-4 resulting in the accumulation of a 25kDa cleaved-Par-4 (cl-Par-4) fragment and we investigated in the present study the mechanisms regulating this fragment using cl-Par-4-expressing stable clones derived from ovarian and endometrial cancer cell lines.Cl-Par-4 protein was weakly express in all stable clones despite constitutive expression. However, upon cisplatin treatment, cl-Par-4 levels increased up to 50-fold relative to baseline conditions. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
(95 reference statements)
1
8
0
Order By: Relevance
“…showed that cleaved Par-4 is also regulated by the proteasome. 40 We now report a stimulus-dependent regulation of Par-4 by the proteasome. That stimulus is cisplatin.…”
Section: Discussionmentioning
confidence: 72%
“…showed that cleaved Par-4 is also regulated by the proteasome. 40 We now report a stimulus-dependent regulation of Par-4 by the proteasome. That stimulus is cisplatin.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, this unique mechanism of selectivity has been demonstrated in various models and also seemed to be involved in chemoresistance (including Tamoxifen, taxane and platinum agents) and tumorigenesis mechanisms [ 172 176 ]. As previously described, gynecological tissues are known for being hormone-dependent and, interestingly, it has been demonstrated that estrogen can downregulate Par-4 and thus could be involved in chemoresistance-associated mechanisms [ 177 , 178 ]. A study demonstrated that Par-4 increase the apoptotic response to paclitaxel treatment in ovarian cancer cells [ 179 ].…”
Section: Chemoresistance In Gynecological Cancersmentioning
confidence: 99%
“…Our laboratory recently published a manuscript indicating that the cleaved form of Par-4 was highly reduced/absent in chemoresistant gynecological cancers indicating a potential venue for this protein to overcome this hurdle. This inhibition was post-translational and regulated by the PI3K and MAPK pathways, previously described as being involved in chemoresistance mechanisms [ 178 ]. Except these studies, the role of Par-4 on chemoresistance in gynecological cancer has received very little attention.…”
Section: Chemoresistance In Gynecological Cancersmentioning
confidence: 99%
“…Later, Treude et al demonstrated that caspase-8 also generates cl-Par-4 in response to TNFαand UV-induced apoptosis 67 . Indeed, cl-Par-4 was generated in response to a variety of anticancer agents effectively eliminating the cancer cells 33,34,[67][68][69][70] .…”
Section: Caspase-mediated Cleavage Of Par-4: the Cut That Always Bleedsmentioning
confidence: 99%